State Of Knowledge Study From The Chemical Experiment Theme (Research, Society and Development, 2019)
Chemistry in present in many ways in our daily lives. Many theoretical aspects can be explained and exemplified from everyday observations, which can contribute to a dynamic learning of content in this area, making it easier. Because it is also an experimental science, in addition to everyday approaches in the explanation of content, practical classes can also contribute to a better assimilation of the theoretical concepts of Chemistry. Based on the use of experimentation as a tool to improve learning in chemistry teaching, the present work aims to make a systematic literature review of the Journals Educación Química, Areté e Química Nova na Escola, Qualis A1, A2 e B1, respectively, and in the dissertations of the IFCE – Campus Fortaleza’s Graduate in Science and Mathematics Teaching Program. 7 materials were selected, of which 5 are articles of the cited journals and 2 are dissertations of the Graduate Program. The works were analyzed regarding the research and teaching methodologies used in the application of the study. All the authors agree that the experimentation allied to the contextualization with the daily lives phenomena contributes to an improvement in the learning in the teaching of Chemistry.